Elder abuse among rural community dwellling elders in Kuala Pilah District, Negeri Sembilan state, Malaysia / Rajini Sooryanarayana. - Rajini , Sooryanarayana (2016)
Background: The increasing ageing population, coupled with urbanisation, rapid development and changes in the traditional family structure has led to various conflicts within families, social networks and health care systems. As Malaysia is fast approaching an ageing nation status, the health, safety and welfare of elders are major concerns to society. Elder abuse and neglect is a phenomenon recognised in some parts of the world but less so locally. This is the first community based study to be undertaken on elder abuse in Malaysia. Aim: To describe the prevalence of elder abuse among rural community dwelling elders, determine associated factors; describe the pattern of disclosure of abuse and the characteristics of perpetrators. Design: This study consisted of three phases. Phase one was a systematic review on the prevalence and measurement of elder abuse. Phase two was a pilot study, validating the questionnaire to be used in the next phase. Phase three was a cross-sectional study conducted in the community of Kuala Pilah district, Negeri Sembilan state, which consisted predominantly of rural populace. A total of 2,496 elders were approached in a multi-stage random sample of community dwelling elders in selected households using the sampling frame of the national census provided by the Department of Statistics, Malaysia. Face-to-face interviews guided by a structured questionnaire were conducted over a period of six months from November 2013 to May 2014. Cognition, depression, anxiety, stress, physical health status, mental health status, disability, physical function, mobility-disability and risk of social isolation were assessed, besides chronic disease, current employment, and history of abuse, among other sociodemographic features. Results: The prevalence of overall abuse was reported to be 4.5% in the past 12 months, with psychological abuse being the most common form followed by financial, physical, neglect and sexual abuse. In the multivariate analysis, males (aOR 1.70, 95% CI 1.05- iv 3.06), secondary or higher level education (aOR 2.13, 95% CI 1.03-4.42), poor mental health status (aOR 4.14, 95% CI 2.18-7.87), risk of social isolation (aOR 2.67, 95% CI 1.42-5.02), a prior history of abuse (aOR 4.29, 95% CI 1.72-10.69) and depressive symptoms (aOR 11.78, 95% CI 4.08-34.06) were found to be associated with overall abuse. Most elders disclosed abusive events to other family members, with various actions ensuing to approach or avoid the perpetrator. Perpetrators tended to be males and from amongst family members, specifically adult children, with abuse usually occurring at the elder’s home. Conclusion: Elder abuse occurred among one in every twenty elders. Early screening especially for elders with depressive symptoms, poorer mental health status and prior history of abuse may help to identify elders at risk of elder abuse. Home visits may be helpful to detect elders at risk of isolation. Improving social support of elders can alleviate the burden of family caregivers, especially as perpetrators are largely family members. A multidisciplinary effort by social and health care workers with better legal provisions would serve to help prevent this phenomenon from occurring and better protect those affected, with future research specifically looking into this issue.